Measurement of the W+W− production cross section in pp collisions at a centre-of-mass energy of √s = 13 TeV with the ATLAS experiment - Alconada Verzini, María Josefina (2017)
The production of opposite-charge W -boson pairs in proton–proton collisions at √s = 13 TeV is measured using data corresponding to 3.16 fb−1 of integrated luminosity collected by the ATLAS detector at the CERN Large Hadron Collider in 2015. Candidate W -boson pairs are selected by identifying their leptonic decays into an electron, a muon and neutrinos. Events with reconstructed jets are not included in the candidate event sample. The cross-section measurement is performed in a fiducial phase space close to the experimental acceptance and is compared to theoretical predictions. Agreement is found between the measurement and the most accurate calculations available.